2021
DOI: 10.3390/membranes11080582
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an Integrated and Sustainable Multistage System for the Treatment of Poultry Slaughterhouse Wastewater

Abstract: This paper assesses the performance of an integrated multistage laboratory-scale plant, for the treatment of poultry slaughterhouse wastewater (PSW). The system was comprised of an eco-flush dosed bio-physico pre-treatment unit for fats, oil, and grease (FOG) hydrolysis prior to the PSW being fed to a down-flow expanded granular bed reactor (DEGBR), coupled to a membrane bioreactor (DEGBR-MBR). The system’s configuration strategy was developed to achieve optimal PSW treatment by introducing the enzymatic pre-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The high concentrations of organic matter in the form of FOG present a challenge associated with the treatment of PSW [22]. Hence, a pre-treatment unit may be required [12,13].…”
Section: Characteristics Of Poultry Slaughterhouse Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…The high concentrations of organic matter in the form of FOG present a challenge associated with the treatment of PSW [22]. Hence, a pre-treatment unit may be required [12,13].…”
Section: Characteristics Of Poultry Slaughterhouse Wastewatermentioning
confidence: 99%
“…In this context, biological systems under aerobic conditions using EcoFlush TM (a novel bacteria-enzymatic consortium blend that is used for the remediation of hydrocarbons) can achieve high organic matter and nutrient removal efficiencies. This technology has already showcased its efficacy in remediating PSW [12,13]. The studies reported removal efficiencies of 38-56% TSS, 50-70% COD, and 80-82% FOG.…”
Section: Introductionmentioning
confidence: 98%
“…A study done by [36] a pre-treatment using an Ecoflush bioremediation agent was implemented and resulted in FOG removal of 80% and the TSS and COD removal which reached 38% and 56%, respectively, before feeding the slaughter wastewater into the anaerobic digester. Meyo, Njoya [32] also did a similar study on the pre-treatment of Poultry Slaughter Wastewater (PSW), and the removal percentages varied between 20 and 50% for total suspended solids (TSS), 20 and 70% for chemical oxygen demand (COD), and 50 and 83% for fats, oil, and grease (FOG) before anaerobic treatment using an EGSB reactor.…”
Section: Aeration Pretreatment Using Enzymesmentioning
confidence: 99%
“…The use of multi integrated systems provide a significant impact on the effluent quality. Dyosile, Mdladla [36] had a higher overall removal efficiency when an integrated system of using enzymatic pre-treatment-DEGBR-MBR was analyzed as compared to anaerobically digesting the poultry slaughterhouse wastewater (PSW) with the DEGBR with no prior or post treatment. The pre-treatment had FOG removal of 80% and the TSS and COD removal reached 38% and 56%, respectively.…”
Section: Multi-integrated Systemsmentioning
confidence: 99%
“…Moreover, it causes infection-related health risks for humans and animals using contaminated water, as well as problems such as congestion and foam formation in the drainage systems of wastewater treatment plants, due to excess nitrogen and phosphorus in their content (Cao et al, 2021;Garcia et al, 2020). Therefore, the urgency to develop an efficient, environmentally friendly and innovative advanced treatment technology to reach specific discharge limits and to ensure sustainable economic growth is inevitable (Dyosile et al, 2021).…”
Section: Introductionmentioning
confidence: 99%